Assessment of Ovarian Function in Phase III (Neo)Adjuvant Breast Cancer Clinical Trials: A Systematic Evaluation. (28th May 2021) - Cui, Wanyuan; Francis, Prudence A; Loi, Sherene; Hickey, Martha; Stern, Catharyn; Na, Lumine; Partridge, Ann H; Loibl, Sibylle; Anderson, Richard A; Hutt, Karla J; Keogh, Louise A; Phillips, Kelly-Anne
Abstract: Background: Loss of ovarian function is a recognized adverse effect of chemotherapy for breast cancer and of great importance to patients. Little is known about the ovarian toxicity of newer cancer treatments. This study examined whether breast cancer clinical trials include assessment of the impact of trial interventions on ovarian function. Methods: Eligible trials were phase III (neo)adjuvant trials of pharmacologic treatments for breast cancer, recruiting between June 2008 and October 2019, which included premenopausal women. MEDLINE, EMBASE, Clinicaltrials.gov, and EudraCT were searched. Data were extracted from trial publications, protocols, databases, and a survey sent to all trial chairs. Tests of statistical significance were 2-sided. Results: Of 2354 records identified, 141 trials were eligible. Investigational treatments included chemotherapy (36.9%), HER2 targeted (24.8%), endocrine (12.8%), immunotherapy (7.8%), cyclin-dependent kinase 4/6 inhibitors (5.0%), and poly-ADP-ribose polymerase inhibitors (2.8%). Ovarian function was a prespecified endpoint in 13 (9.2%) trials. Forty-five (31.9%) trials collected ovarian function data, but only 33 (23.4%) collected posttrial-intervention data. Common postintervention data collected included menstruation (15.6%), pregnancy (13.5%), estradiol (9.9%), and follicle-stimulating hormone levels (8.5%). Only 4 (2.8%) trials collected postintervention anti-müllerian hormone levels, and 3 (2.1%) trials collected antral follicle count. Of 22 trials investigating immunotherapy, cyclin-dependent kinase 4/6 inhibitors, or poly-ADP-ribose polymerase inhibitors, none specified ovarian function as an endpoint, but 4 (18.2%) collected postintervention ovarian function data. Conclusions: The impact of pharmacologic interventions on ovarian function is infrequently assessed in phase III breast cancer (neo)adjuvant trials that include premenopausal women. Trialists should consider inclusion of ovarian function endpoints when designing clinical trials, given its importance for informed decision making.